Lessons for sustainability – Failing to scale ICT4Ag-enabled services - Shepherd, Andrew (Technical Centre for Agricultural and Rural Cooperation, 2016)
ICTs have undoubted potential to boost agricultural production and value chains in ACP countries. But many efforts to introduce ICTs for this purpose have not been sustainable. What can we learn from their experiences? The stories in this booklet stress the importance of understanding the intended users, ensuring economic viability, fully promoting the service, and making sure the technology offered is the right solution to the problem.